Cosmic noise : a history of early radio astronomy - Sullivan, Woodruff Turner (Cambridge, UK ; New York : Cambridge University Press, 2009)
"Providing a definitive history of the formative years of radio astronomy, this book is invaluable for historians of science, scientists and engineers. The whole of worldwide radio and radar astronomy is covered, beginning with the discoveries by Jansky and Reber of cosmic noise before World War II, through the wartime detections of solar noise, the discovery of radio stars, lunar and meteor radiation experiments, the detection of the hydrogen spectral line, to the discoveries of Hey, Ryle, Lovell and Pawsey in the decade following the war, revealing an entirely different sky from that of visual astronomy. Using contemporary literature, correspondence and photographs, the book tells the story of the people who shaped the intellectual, technical, and social aspects of the field now known as radio astronomy. The book features quotes from over a hundred interviews with pioneering radio astronomers, giving fascinating insights into the development of radio astronomy. - Includes an annotated table of contents as well as a chronological list of references to help the reader trace the history of the subject through key publications - Features quotes from over 100 interviews with pioneering radio astronomers - Uses literature, correspondence and over 180 photographs and illustrations from many sources to tell the fascinating story of radio astronomy"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Radio astronomy -- History